Microbial composition of egg component and its association with hatchability of laying hens - Jin, Jiaming; Zhou, Qianqian; Lan, Fangren; Li, Junying; Yang, Ning; Sun, Congjiao (Frontiers in Microbiology, 2022)
The internal quality of eggs is critical for human consumption and embryonic development. However, microorganisms inside eggs have not been thoroughly investigated as a factor in determining the internal quality of eggs. Here, we selected 21 chickens based on the hatching results from pedigree insemination of more than 1,000 chickens and divided them into high hatchability and low hatchability. Then collect 74 eggs and obtain egg whites and yolks, of which 52 were fresh eggs and 18 were eggs that have been incubated for 12 days. We characterized the microbial composition of egg yolks and whites, the longitudinal and horizontal changes of microbes, and differences in microbe abundance between high and low hatchability groups. The results indicated that egg white is not sterile and has lower microbial diversity than egg yolk, due to the presence of antibacterial substances such as lysozyme. After a 12-day incubation period, the microbial diversity of egg white decreased dramatically, whereas the microbial diversity of egg yolk increased slightly. There was a large difference in the microbial composition of egg whites and yolks, and this difference increased after 12 days of incubation. Moreover, Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes were typically the dominant phyla in egg yolk and white. Additionally, comparing high and low hatchability groups, Rothia more existed in the fresh egg yolk of low hatchability groups and was considered to have low virulence. Muribaculaceae was identified as a biomarker bacteria in egg yolks incubated for 12 days which are more often detected in healthy control groups and may relate to extending lifespan. These findings shed light on the composition and differences of microbiota between the egg yolk and white and may open up new avenues for studying embryonic development in chicks.